Variasi Motif Batik Palembang Menggunakan Sistem Fungsi Teriterasi dan Himpunan Julia - Eka Susanti (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2015)
Batik Palembang has a distinctive design with bright colour. There are several design, in this research, can be visualized songket batik design and jumputan batik design. Jumputan and songket batik design with the help of the software can be visualized using iterated function systems (IFS) and the Julia set. Songket batik design can be visualized with a combination of Sierpinski Carpet and Julia set while jumputan battik design can be visualized with a combination of some of the Julia set.